Communicable behavior of non-communicable diseases - Shukla, Prashant; Gupta, Anita; Sehgal, Vijay K.; Kumar, Raghuvansh (International Journal of Basic & Clinical Pharmacology, 2017)
Communicability of non- communicable diseases can be explained using the prototype of non- communicable diseases. The concept can be further extended to other non- communicable diseases. Diabetes mellitus (DM) is regarded as the prototype of non-communicable diseases. Its subtype, type 2 DM is usually associated with obesity. Obesity, in turn, can be attributed to deranged eating habits and lack of physical activity. Eating habits of a person bears a close resemblance to the parental eating habits. Other factors contributing to obesity like alcoholism can also be transmitted from parents to child. Smoking, another factor implicated in DM, can be picked as a habit from peer group as well as family. All these factors implicated directly or indirectly in the pathogenesis of DM are actually components of lifestyle. These lifestyle components can be transmitted both in an inter-generation and intra-generation fashion. And so the chances of transmission of DM (a lifestyle disease) in the same fashion cannot be ruled out.